Investment in infrastructure and trade: The case of ports - Giulia Brancaccio; Myrto Kalouptsidi; Theodore Papageorgiou (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
Transportation infrastructure is vital for the smooth functioning of international trade. Ports are a crucial gateway to this system: with more than 80% of trade carried by ships, they shape trade costs, and it is critical that they operate efficiently. Yet ports are susceptible to disruptions, causing costly delays. With enormous budgets spent on infrastructure to alleviate these costs, a key policy question emerges: in a world with high volatility, what are the returns to investing in infrastructure? To address this question, we introduce an empirical framework that combines insights from queueing theory to capture port technology, with tools from demand estimation. We use our framework, together with a collection of novel datasets, to quantify the costs of disruptions and evaluate transportation infrastructure investment. Our analysis unveils four policy-relevant messages: (i) investing in port infrastructure can lead to substantial trade and welfare gains, but only if targeted properly- in fact, net of costs, the marginal return to investment is positive at a minority of US ports; (ii) there are sizable spillovers across ports, as investing in one port can decongest a wider set of ports, suggesting that decision-making should not be decentralized to local authorities; (iii) the economies of scale arising from queuing would lead a planner to concentrate investment in large, geographically dispersed megaports; (iv) macroeconomic volatility can drastically change returns to investment.
Keywords: 330; transportation; infrastructure; ports; congestion; macroeconomic volatility; disruptions; spillovers